Probing into Bifunctional Luminomagnetic Upconverting Nanorods for External Magnetic Tracking Applications - Singh S.; Ghorai B.; Kumar Yadav P.; Kumar Ghorai U.; Upadhyay C.; Gupta B.K. (My University, 2025)
A strategy to synthesize a bi-functional luminomagnetic Er3+/Yb3+-doped NaGdF4 nanorods, using a facile base-catalyzed hydrothermal method, is demonstrated. This luminomagnetic nanorods material is investigated for its structural/microstructural, optical, and magnetic properties to validate applications in the bio-medical field. The as-synthesized nanorods exhibit highly intense green emission peaking at 539 nm upon excitation with 980 nm wavelength using a diode laser. Further, the effect of 980 nm laser power on the emission spectrum of these Er3+/Yb3+-doped NaGdF4 nanorods is investigated and a mechanism for the upconversion process is proposed. The CIE (French: International Commission on Illumination) coordinates at all the input laser powers lie in the close vicinity of x=0.28 and y=0.68 and thus suggest the color purity of the Er3+/Yb3+-doped NaGdF4 nanorods. Moreover, these nanorods also exhibit strong paramagnetic behavior as confirmed by M−H and M−T measurements. We have also demonstrated the application of these nanorods for external magnetic field tracking applications. The cellular cytotoxicity analysis of the nanorods against the MDA-MB-231 and MCF-10 A cell lines suggests their applicability in biomedical applications. Thus, the co-existence of luminescence and magnetism in a single entity suggests its suitability as a bi-functional nanoprobe in biological applications. © 2020 Wiley-VCH GmbH